Design and implementation of a mobile application for public transportation services in tourist destination area - Sazilah Salam; Norazlina Shafie; Emaliana Kasmuri; Jack Febrian Rusdi (Institute of Advanced Engineering and Science, 2026)
Efficient public transportation is important for tourism cities like Melaka, Malaysia, where fragmented services and limited real-time information reduce user satisfaction and contribute to congestion. Existing transport applications often focus on a single mode and provide limited tourist-oriented functions. This study designed and implemented myGPT, a mobile application that integrates bus, taxi, and trishaw services into a unified platform with real-time information, cashless payment, and social interaction features. Using a design, development, and research (DDR) approach, user requirements were identified through a literature review and surveys, followed by system design, prototype development, and pilot testing. The myGPT framework includes modules for multimodal service discovery and trip planning, GPS-based nearby vehicle visibility, QR-code payment, and in-app communication and feedback. Pilot implementation results indicate improved trip coordination, usability, and user trust. The findings suggest that combining multimodal integration, real-time tracking, payments, and social features can support smarter tourist mobility and encourage sustainable urban transport in heritage cities.